2013
DOI: 10.1016/j.marpolbul.2013.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Critical research needs for identifying future changes in Gulf coral reef ecosystems

Abstract: Expert opinion was assessed to identify current knowledge gaps in determining future changes in Arabian/ Persian Gulf (thereafter ‘Gulf’) coral reefs. Thirty-one participants submitted 71 research questions that were peer-assessed in terms of scientific importance (i.e., filled a knowledge gap and was a research priority) and efficiency in resource use (i.e., was highly feasible and ecologically broad). Ten research questions, in six major research areas, were highly important for both understanding Gulf coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…I examined 28 different reports and articles that over the last 8 years identified research questions or issues with potential salience to ocean sustainability. Those included: 13 general (i.e., non-marine) big question exercises (Sutherland et al, 2006(Sutherland et al, , 2009(Sutherland et al, , 2012b(Sutherland et al, , 2013bMorton et al, 2009;Brown et al, 2010;Pretty et al, 2010;Fleishman et al, 2011;Kark et al, 2011;Rudd et al, 2011;Boxall et al, 2012;Braunisch et al, 2012;Ingram et al, 2013) and five specific to coastal and marine issues (Fissel et al, 2012;Feary et al, 2013;Rees et al, 2013;Parsons et al, 2014;Vugteveen et al, 2014); six annual horizon scanning exercises (Sutherland et al, 2008(Sutherland et al, , 2011a(Sutherland et al, , 2012a(Sutherland et al, , 2013a(Sutherland et al, , 2014; and four oceanspecific reports that identified important research questions and that were based on expert opinions (Heip et al, 2011;Heip and McDonough, 2012;Snelgrove et al, 2012;Borja et al, 2013).…”
Section: Research Question Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…I examined 28 different reports and articles that over the last 8 years identified research questions or issues with potential salience to ocean sustainability. Those included: 13 general (i.e., non-marine) big question exercises (Sutherland et al, 2006(Sutherland et al, , 2009(Sutherland et al, , 2012b(Sutherland et al, , 2013bMorton et al, 2009;Brown et al, 2010;Pretty et al, 2010;Fleishman et al, 2011;Kark et al, 2011;Rudd et al, 2011;Boxall et al, 2012;Braunisch et al, 2012;Ingram et al, 2013) and five specific to coastal and marine issues (Fissel et al, 2012;Feary et al, 2013;Rees et al, 2013;Parsons et al, 2014;Vugteveen et al, 2014); six annual horizon scanning exercises (Sutherland et al, 2008(Sutherland et al, , 2011a(Sutherland et al, , 2012a(Sutherland et al, , 2013a(Sutherland et al, , 2014; and four oceanspecific reports that identified important research questions and that were based on expert opinions (Heip et al, 2011;Heip and McDonough, 2012;Snelgrove et al, 2012;Borja et al, 2013).…”
Section: Research Question Identificationmentioning
confidence: 99%
“…In recent years, an increasing number of bottom-up, participatory horizon scanning and "big question" exercises have also taken place. Those efforts, while usually not ocean-specific (but see Fissel et al, 2012;Feary et al, 2013;Rees et al, 2013;Parsons et al, 2014), represent the collective insights of thousands of scientists and have identified many important ocean-and coastal-oriented research questions (Sutherland et al, 2006(Sutherland et al, , 2009(Sutherland et al, , 2013bPretty et al, 2010;Fleishman et al, 2011;Rudd et al, 2011;Boxall et al, 2012;Ingram et al, 2013). With ongoing international efforts to set ocean research direction for the coming decades (e.g., the USA Decadal Survey of Ocean Sciences 2015 [nassites.org/dsos2015/] and Future Earth [www.futureearth.info/]) it is timely to take stock of the opinions of scientists and policymakers who participated in the numerous bottom-up horizon scanning and big question exercises.…”
Section: Introductionmentioning
confidence: 99%
“…This resonates with many recent attempts that aim to distil 'major challenges' or 'big questions' from the marine scientific community directly through so-called bottom-up, participatory surveys or exercises [18,21,23,8,9]. A particular objective of these efforts is to take stock of the variety of perceptions and opinions of marine scientists from different academic disciplines to better understand research priorities.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, monitoring should also be extended to processes and activities that are likely to have significant adverse impacts on the valued ecosystem components in the Arabian Gulf. Feary et al (2013) identified research topics that are considered to be the highest priority areas for future coral reef research in the Arabian Gulf, which could be extend to the other valued ecosystem components. These research areas include marine protected areas development, biological and ecological processes structuring marine ecosystems, climate change impacts on ecology and biology of ecosystems, effects of anthropogenic activities on marine ecosystems, connectivity of coral reef communities, disease biology, economic evaluation of ecosystems functions and services, monitoring and ecological surveys of species and communities, coral reef restoration and management, and mechanisms governing ecosystems' resistance and adaptation to environmental extremes.…”
Section: Integrated Environmental Monitoring and Scientific Researchmentioning
confidence: 99%
“…Due to its unique environmental setting, the Arabian Gulf is increasingly receiving international scientific interest to study the effects of environmental extremes on marine organisms, and to investigate the potential impacts of future climate change on the ecological integrity of marine ecosystems (Riegl and Purkis, 2012;Feary et al, 2013). This chapter identifies valued ecosystem components in the Arabian Gulf, characterizes natural and anthropogenic impacts on these ecosystems, and suggests measures for conservation that might contribute to the protection of the fragile marine ecosystems in the Arabian Gulf.…”
Section: Introductionmentioning
confidence: 99%